2020
DOI: 10.1051/e3sconf/202018503035
|View full text |Cite
|
Sign up to set email alerts
|

A Score Level Fusion Method on Fingerprint and Finger Vein

Abstract: In this paper, we represent a score level fusion method on fingerprint and finger vein. Each unimodal identification system carries out processes of image preprocessing, feature extraction and feature matching to generate a vector of score. And we apply clustering analysis to split the score range into zones of interest. Then a decision tree and weighted-sum approach are used to make the decision. We test the proposed method on standard biometric database. Three metrics, namely, False Accept Rate, False Reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The main finding of their study was that using Borda count, logistic regression, and the average sum method gave an accuracy of 93.33%, 96.67%, and 96.67%, respectively. On the other hand [23], Peng et al showed how to combine the score vectors of a fingerprint and a finger vein at the level. Each unimodal identification system was executed independently to produce a score vector.…”
Section: Multimodal Biometric Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of their study was that using Borda count, logistic regression, and the average sum method gave an accuracy of 93.33%, 96.67%, and 96.67%, respectively. On the other hand [23], Peng et al showed how to combine the score vectors of a fingerprint and a finger vein at the level. Each unimodal identification system was executed independently to produce a score vector.…”
Section: Multimodal Biometric Fusionmentioning
confidence: 99%
“…There is a need for score normalization after evaluating match scores from each modality [40]. In general, normalization aims to set the mean and variance of datasets to particular values [23]. Therefore, during this part of the experiment, before combining the scores inferred from the Hard BioHash query and the Soft BioHash query, we use the median and median absolute deviation (MAD) technique as a score normalization that can change the scores of several systems into a common domain.…”
Section: Third Experiment: Retrieving Face Image Utilizing Proposed H...mentioning
confidence: 99%
“…Here, face and fingerprint biometrics traits are fused using match score level fusion based on weighted Sum-Rule. There are four main categories of fusion techniques: sensor level fusion, feature level fusion, match score level fusion, and decision level fusion (Peng et al, 2020). First, match score level fusion is adopted to fuse both biometrics traits.…”
Section: Introductionmentioning
confidence: 99%